INTEGRASI BEBRAS TASK DALAM PERANGKAT PEMBELAJARAN: PELATIHAN GURU SD DI KOTA MAKASSAR UNTUK PENGUATAN COMPUTATIONAL THINKING - Abdal, Nurul Mukhlisah; Setialaksana, Wirawan; Syawaluddin, Ahmad; Afifah, Fadhillah; Marhayati (Jurnal Edukasi dan Pengabdian kepada Masyarakat, 2025)
This community service program aims to enhance the competencies of elementary school teachers in Makassar City in integrating Computational Thinking (CT) into instructional materials through the use of Bebras Tasks. The program was implemented through five systematic stages: socialization, training, technology application, mentoring and evaluation, and sustainability. The training covered the development of Bebras problems, preparation of lesson plans (RPP), student worksheets (LKS), and CT-based assessment rubrics aligned with the Merdeka Curriculum. The results indicate a significant improvement in teachers’ ability to design CT-oriented learning materials, along with a 22–30% increase in students’ computational thinking skills based on pretest and posttest data. In addition to producing a Bebras problem bank and a complete set of instructional tools, the program successfully established a CT working group (Pokja) to ensure long-term sustainability. Overall, this program positively contributes to improving learning quality and strengthening teachers’ professional capacity.